Interaktive Programmierungsansätze für die Gestaltung von Agrar- und Umweltprogrammen; Interactive Programming in Agricultural and Environmental Programme Planning - Dieter Kirschke; Kurt Jechlitschka (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Planning agricultural and environmental programmes has become a complex task. In this paper we show how interactive programming can help to solve such complex policy decision-making problems. The basic linear programming model is implemented with Excel. We show, for a hypothetical agricultural and environmental programme, how the approach can be used in an interactive way between scientists and policy decision-makers. The approach allows to visually demonstrate and quickly assess the consequences of changing assumptions and framework conditions on the programme design. It could effectively improve the quality of policy decision-making support; it requires the actors' willingness, of course, to engage in a real dialogue.
Keywords: 330; Agrarpolitik; Umweltpolitik; EU-Agrarpolitik; Mathematische Optimierung; Politikberatung